Cultivation offers effective management of subterranean clover damping‐off and root disease. (14th February 2017) - You, M. P.; Guo, K.; Nicol, D.; Kidd, D.; Ryan, M. H.; Foster, K.; Barbetti, M. J.
Abstract: Soil cultivation studies involving subterranean clover pastures were undertaken utilizing field cores from five farms and two in‐field trials. Tap and lateral root disease in cores was less ( p < .001) severe and root and shoot weights greater ( p < .001) following simulated cultivation. Germination and severity of root disease were both affected ( p < .005) by three‐way interactions with cultivation, cultivar and field site. Cultivation in cores suppressed tap root disease for cultivars Meteora and Riverina across the five sites and Seaton Park for two sites. In‐field trials confirmed cultivation reduces root disease severity and increases germination and plant productivity. The best in‐field treatment was cultivation + fumigation that reduced ( p < .05) tap and lateral root disease and increased nodulation and root and shoot weights for Riverina, Seaton Park and Woogenellup. Cultivation + fumigation also increased ( p < .05) germination for Woogenellup and Seaton Park. There were negative correlations (all p < .001) between tap and lateral root disease with nodulation ( R 2 = .85, R 2 = .58, respectively); tap root disease with root and shoot weight ( R 2 = .58, R 2 = .854, respectively); and lateral root disease with root and shoot weight ( R 2 = .83, R 2 = .64 respectively). This study highlights the close relationship between severe root disease and reduced nodulation, likely explaining much of the widespread poor nodulation in subterranean clover pastures. This study confirms that damping‐off and root disease can be mitigated by cultivation, offering producers flexibility in disease management, especially where autumn–winter feed shortages occur on a regular basis.